Handwritten Notes for "Groundbreaking" Ceremony - Jane Tolmach:::::: (1973)
Handwritten notes for a speech presented at a groundbreaking ceremony for a Multi-Service Center and a Fire Station in La Colonia neighborhood in Oxnard, California.